Automating time based Household electricity Bill Calculations for Efficient Budgeting - Ravikant Keshav Nanwatkar; Bhosale Sakshi Annasaheb; Kasturi Sanjay Shirbhate; Dhande Dipti Vinod; Vaishnavi Satish Kadam (International Journal of Electrical Power and Machine Systems, 2026)
Recurrent household expenses must be precisely, in time, and openly tracked to make efficient household budgeting. Conventional monthly billing performance tends to delay the financial information, which results in the inefficient cash flow management and inability to modify short-term expenditure patterns. The proposed research is a system to automatize the calculation of household bills per week in order to deliver more frequent and practical insights into the household spending habits. The suggested model is used to gather and process consumption information related to electricity, water, gas, and internet on a weekly basis, which allows the user to monitor costs more closely and make sound financial decisions. The system combines data processing algorithms with a user-friendly interface to create itemized weekly bills, forecast the expenses, and abnormal behavior of consumption. We use simulation and case studies to show that weekly billing is more advantageous to financial awareness and helps adopt more responsive budgeting strategies. Implementation issues, data-related concerns, and possible integration with smart meters and systems based on IoT are also discussed in the paper. We find that the routine household bill calculation automation has a great deal of impact on short-term financial planning and encourages prudent.
Keywords: Automated Expense Tracking; Consumption Monitoring System; Financial Planning and Budgeting; Smart Meter and IoT Integration; Weekly Household Billing